Effectiveness of mindfulness-based interventions on the well-being of healthcare workers: a systematic review and meta-analysis - Julian Thumboo; Hiang Khoon Tan; Chun En Yau; Natasha Yixuan Ong; Finn Jing Jie Teo; Jane Zi Ying Ee; Qin Xiang Ng (General Psychiatry)
Background Growing evidence attests to the efficacy of mindfulness-based interventions (MBIs), but their effectiveness for healthcare workers remains uncertain.Aims To evaluate the evidence for MBIs in improving healthcare workers’ psychological well-being.Methods A systematic literature search was conducted on Medline, Embase, Cumulative Index for Nursing and Allied Health Literature, PsycINFO and Cochrane Central Register of Controlled Trials up to 31 August 2022 using the keywords ‘healthcare worker’, ‘doctor’, ‘nurse’, ‘allied health’, ‘mindfulness’, ‘wellness’, ‘workshop’ and ‘program’. Randomised controlled trials with a defined MBI focusing on healthcare workers and quantitative outcome measures related to subjective or psychological well-being were eligible for inclusion. R V.4.0.3 was used for data analysis, with the standardised mean difference as the primary outcome, employing DerSimonian and Laird’s random effects model. Grading of Recommendations, Assessment, Development and Evaluation framework was used to evaluate the quality of evidence. Cochrane’s Risk of Bias 2 tool was used to assess the risk of bias in the included studies.Results A total of 27 studies with 2506 participants were included, mostly from the USA, involving various healthcare professions. MBIs such as stress reduction programmes, apps, meditation and training showed small to large effects on anxiety, burnout, stress, depression, psychological distress and job strain outcomes of the participants. Positive effects were also seen in self-compassion, empathy, mindfulness and well-being. However, long-term outcomes (1 month or longer postintervention) varied, and the effects were not consistently sustained.Conclusions MBIs offer short-term benefits in reducing stress-related symptoms in healthcare workers. The review also highlights limitations such as intervention heterogeneity, reduced power in specific subgroup analyses and variable study quality.PROSPERO registration number CRD42022353340.